Erratum: delos Angeles, M.D., Buot, I.E. Jr., Moran, C.B., Robinson, A.S. & Tandang, D.N. (2022) Corybas kaiganganianus (Orchidaceae), a new, rare helmet orchid from Samar Island, Philippines. Phytotaxa 543 (2): 127–134. - Delos Angeles, Marjorie D.; Buot Jr., Inocencio E.; Moran, Cecilia B.; Robinson, Alastair S.; Tandang, Danilo N. (Phytotaxa, 2024)
N/A